Development of a single-dose recombinant CAMP factor entrapping poly(lactide-co-glycolide) microspheres-based vaccine against Streptococcus agalactiae. Issue 9 (1st March 2017) - Liu, Gang; Yin, Jinhua; Barkema, Herman W.; Chen, Liben; Shahid, Muhammad; Szenci, Otto; De Buck, Jeroen; Kastelic, John P.; Han, Bo
Highlights: Streptococcus agalactiae vaccine was developed by PLGA microspheres encapsulated CAMP. The slow release kinetics of PLGA-CAMP were demonstrated in vivo and in vitro . Humoral immunity was induced by CAMP factor and PLGA-CAMP in a mouse model. PLGA MS encapsulated CAMP conferred protection against S. agalactiae in a mouse model. Abstract: Streptococcus agalactiae is an important contagious bovine mastitis pathogen. Although it is well controlled and even eradicated in most Northern European and North American dairy herds, the prevalence of this pathogen remains very high in China. However, research on development of a vaccine against S. agalactiae mastitis is scarce. The aims of the present study were to: (1) develop a single-dose vaccine against S. agalactiae based on poly(lactic-co-glycolic acid) (PLGA) microspheres (MS) encapsulated CAMP factor, a conserved virulent protein encoded by S. agalactiae 's cfb gene; and (2) evaluate its immunogenicity and protective efficacy in a mouse model. The cfb gene was cloned and expressed in a recombinant Escherichia coli strain Trans1-T1. The CAMP factor was tested to determine a safe dose range and then encapsulated in MS of PLGA (50:50) to assess its release pattern in vitro and immune reaction in vivo. Furthermore, a mouse model and a histopathological assay were developed to evaluate bacterial burden and vaccine efficacy. In the low dosage range (<100 μg), CAMP factor had no obvious toxicity in mice. The release pattern in vitro was characterized by an initial burst release (44%), followed by a sustained and slower release over 7 wk. In mice immunized with either pure CAMP factor protein or PLGA-CAMP, increased antibody titers were detected in the first 2 wk, whereas only PLGA-CAMP immunization induced a sustained increase of antibody titers. In mice vaccinated with PLGA-CAMP, mortality and bacteria counts were lower (compared to a control group) after S. agalactiae challenge. Additionally, no pathological lesions were detected in the vaccinated group. Therefore, PLGA-CAMP conferred protective efficacy against S. agalactiae in our mouse model, indicating its potential as a vaccine against S. agalactiae mastitis. Furthermore, the slow-release kinetics of PLGA MS warranted optimism for development of a single-dose vaccine.